MGE2: A framework for cradle-to-cradle design (2015)
Design and ecology are critical issues in the industrial sector. Products are subject to constant review and optimization for survival in the market, and limited by their impact on the planet. Decisions about a new product affect its life cycle, consumers, and especially the environment. In order to achieve quality solutions, eco-effectiveness must be considered, therefore, in the design of a process, its product development and associated system. An orderly methodology is essential to help towards creating products that meet both user needs and current environmental requirements, under paradigms that create environmental value. To date, the industry has developed techniques in an attempt to address these expectations under Cradle-to-Cradle (C2C), which is loosely structured around the conceptual frameworks and design techniques. The present work describes a new framework that encompasses all stages of design, and enables interaction under a set of principles developed for C2C. Under this innovative new paradigm emerges the Genomic Model of Eco-innovation and Eco-design, proposed as a methodology for designing products that meet individual and collective needs, and which enables the design of eco-friendly products, by integrating them into the framework of the ISO standards of Life Cycle Assessment (LCA), eco-design, eco-labeling, and C2C certification.